On the Moral Duty to Cite Colleagues and Other Virtues of Philosophers - Saja, Krzysztof (Roczniki Filozoficzne, 2025)
The article argues in favor of the thesis that there is an ethical obligation to cite colleagues in academic writing. Recognizing the importance of truth, objectivity, and impartiality, the author also points out the danger of an “excess” of misinterpreted impartiality in philosophical research. He argues that the lack of references to local scholars in Polish philosophical discourse constitutes a manifestation of academic dishonesty, contributing to an artificial “pseudo-dialogue” with international authorities while simultaneously neglecting national debates. While the internationalization of science is important, excessive objectivity and detachment from local discussions weaken intellectual creativity and the coherence of the academic community. The article draws on classical ethical theories to demonstrate that citing colleagues is not only a matter of fairness and gratitude but also a crucial element in fostering a vibrant scholarly dialogue.